Factors associated with an increase in alcohol consumption and tobacco use during the COVID-19 pandemic: A cross-sectional study of data from 105 countries - Quadri Mir Faeq A; Lusher Joanne; Folayan Morenike O; El Tantawi Maha; Zuñiga Ariel A; Brown Brandon; Aly Nourhan M; Okeibunor Joseph C; Florencia Giuliana; Jafer Mohammed; Ara Eshrat; Miranda Kessketien A; et al. (United Kingdom, 2025)
Introduction: The COVID-19 pandemic has inevitably led to monumental challenges, and alcohol drinking and tobacco use have unlikely been spared. This cross-sectional survey reports on factors associated with an increase in alcohol drinking and tobacco use during the COVID-19 pandemic.
Methods: An online survey conducted in 2020, generated data from 14899 adults residing in 105 countries. Dependent variables were changes in alcohol drinking and tobacco use. Independent variables were age, sex, education level, job loss, lost or reduced wages, investment/retirement benefits, interrupted substance addiction care, and income level of the countries. Multilevel logistic regression analysis was computed to explore the associations between dependent and independent variables in adjusted models using the backward stepwise method. The probability of including or excluding a covariate was set at p(in)<0.05 and p(out)>0.1, respectively.
Results: Of the regular alcohol consumers (N=4401), 22.9% reported an increase in their alcohol drinking. Of the regular tobacco users (N=2718), 31% reported an increase in their tobacco use. Job loss (Alcohol: AOR=1.26; Tobacco: AOR=1.32) and lost/reduced wages (Alcohol: AOR=1.52; Tobacco: AOR=1.52) were associated with higher odds of increased alcohol drinking and tobacco use. Many interruptions to addiction care (AOR=1.75) were associated with higher odds of increased alcohol drinking. Whereas no interruption to addiction care was associated with lower odds of increased alcohol drinking (AOR=0.77). Also, none (AOR=0.66) or some (AOR=0.70) interruptions to addiction care were associated with lower odds of increased tobacco use.
Conclusions: This global survey alludes to the unintended consequences of the current COVID-19 pandemic on alcohol drinking and tobacco use. It is critical that the strategies for emergency responses should include support to ameliorate the impact of financial distress and disruption in substance dependence treatment services.